O dwóch wieczorach autorskich Wisławy Szymborskiej - Brzozowski, Jacek (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 1998)
My reading of the following poems Wieczór autorski [An Author Reading], from the volume Sól [Salt], 1962; and Trema [Stage Fright], from the volume Ludzie na moście [People on the Bridge], 1986, is an attempt to define, at least in outline, the essence of the transformation which has occurred in the works by the author of Koniec i początek [The End and the Beginning] over the last several dozen years. The essence of the transformation is gradualy opening of Wisława Szymborska’s poems to the sphere of metaphysics or - as she herself put it in one of the interviews - a quest for ‘the less obvious which does exist in us, in our consciousness’.